The signaling, screening, and human capital effects of National Board certification: Evidence from Chicago and Kentucky high schools - Lisa Barrow; Linda C. Cavalluzzo; Thomas Geraghty; Christine Mokher; Lauren Sartain (Federal Reserve Bank of Chicago, 2020)
The National Board for Professional Teaching Standards recognizes teachers who meet performance standards for "accomplished" educators. States and districts provide support for teachers to obtain this certification, which is considered an honor in the field. Using high school data from Chicago and Kentucky, we examine whether participation in the time- and resource-intensive certification process improves teacher productivity and, ultimately, if recognized teachers are of higher quality than their non-certified peers. We find the certification process itself did not increase teacher productivity. Further, we find mixed evidence on whether certified teachers are more effective at raising test scores than non-certified teachers.
Keywords: 330; Lehrkräfte; Standardisierung; Arbeitsproduktivität; Dienstleistungsqualität; Chicago (Ill.); Kentucky